Proceedings of the Workshop on Eye Movements in Programming, EMIP@ETRA 2018, Warsaw, Poland, June 15, 2018

Computer Science Education: Perspectives on Teaching and learning in school - Sentance, Sue; Barendsen, Erik; Schulte, Carsten

A Framework for Computing Education: Hybrid Interaction System: The need for a bigger picture in computing education - Schulte, Carsten; Budde, Lea (Koli Calling)

The computing repair cafe - Schulte, Carsten; Krüger, Jessica; Gödecke, Andreas; Schmidt, Ann-Katrin (Proceedings of the 13th Workshop in Primary and Secondary Computing Education)

Drafting a Data Science Curriculum for Secondary Schools - Heinemann, Birte; Opel, Simone Anna; Budde, Lea; Schulte, Carsten; Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Wassong, Thomas (Koli Calling)

Paderborn Symposium on Data Science Education at School Level 2017: The Collected Extended Abstracts - Biehler, Rolf; Budde, Lea; Frischemeier, Daniel; Heinemann, Birte; Podworny, Susanne; Schulte, Carsten; Wassong, Thomas
Data science is increasingly relevant in more and more areas of everyday life - but the general education at school so far has hardly responded to these specific changes in digitalization. Completely new challenges for the teaching of mathematics and computer science have emerged, as well as for the subjects of the social and cultural sciences field and for cross-curricular media education. All these subjects have to be reinterpreted in regard to the raising attention to data science, to big data and in regard to a fundamentally changing world of labor and economy. As a reaction, schools have to realize a broad general education that is to be newly defined on the one hand. On the other hand, school education has to stimulate and promote interest in the current, exciting and dynamic new scientific area of data science with its numerous applications. This book presents the extended abstracts of the presentations at a symposium held in November 2017, discussing economic, social and cultural impacts of big data and data science with experts in curriculum development and educational research in statistics and computer science as well as experts from different facets of data science and its applications. Moreover, analyses from a socio-cultural perspective were included. The main goal was to inspire ideas for teaching data science in secondary schools.

The design and exploration cycle as research and development framework in computing education - Schulte, Carsten; Magenheim, Johannes; Müller, Kathrin; Budde, Lea (2017 (IEEE) Global Engineering Education Conference (EDUCON) 2017, Athens, Greece, April 25-28, 2017)

Zieldimensionen für frühe informatische Bildung im Kindergarten und in der Grundschule - Bergner, Nadine; Köster, Hilde; Magenheim, Johannes; Müller, Kathrin; Romeike, Ralf; Schroeder, Ulrik; Schulte, Carsten (Informatische Bildung zum Verstehen und Gestalten der digitalen Welt, Proceedings der 17. GI-Fachtagung Informatik und Schule, (INFOS) 2017, 13.-15. September 2017, Oldenburg)

Ein Modell zur Analyse von Vorstellungen über Roboter und ihrer Funktionsweise - Müller, Kathrin; Schulte, Carsten (Informatische Bildung zum Verstehen und Gestalten der digitalen Welt, Proceedings der 17. GI-Fachtagung Informatik und Schule, (INFOS) 2017, 13.-15. September 2017, Oldenburg)

A theory based tool set for analysing reading processes in the context of learning programming - Budde, Lea; Heinemann, Birte; Schulte, Carsten (Proceedings of the 12th Workshop on Primary and Secondary Computing Education, WiPSCE 2017, Nijmegen, The Netherlands, November 8-10, 2017)

Zieldimensionen informatischer Bildung im Elementar-und Primarbereich - Bergner, Nadine; Köster, Hilde; Magenheim, Johannes; Müller, Kathrin; Romeike, Ralf; Schroeder, Ulrik; Schulte, Carsten (Frühe informatische Bildung - Ziele und Gelingensbedingungen für den Elementar- und Primarbereich. Berlin)

Kompetenzbasierte Gestaltungsempfehlungen für Informatik-Tutorenschulungen - Danielsiek, Holger; Hubwieser, Peter; Krugel, Johannes; Magenheim, Johannes; Ohrndorf, Laura; Ossenschmidt, Daniel; Schaper, Niclas; Vahrenhold, Jan (INFORMATIK 2017)

PERSPECTIVES FOR AN INTERDISCIPLINARY DATA SCIENCE CURRICULUM IN GERMAN SECONDARY SCHOOLS - Biehler, Rolf; Schulte, Carsten (Paderborn Symposium on Data Science Education at School Level)

Eye movements in code reading: relaxing the linear order - Busjahn, Teresa; Bednarik, Roman; Begel, Andrew; E. Crosby, Martha; H. Paterson, James; Schulte, Carsten; Sharif, Bonita; Tamm, Sascha (ICPC)

Proceedings of the 2015 ACM Conference on Innovation and Technology in Computer Science Education, ITiCS 2015, Vilnius, Lithuania, July 4-8, 2015

What influences dwell time during source code reading?: analysis of element type and frequency as factors - Busjahn, Teresa; Bednarik, Roman; Schulte, Carsten (ETRA)

Eye tracking in computing education - Busjahn, Teresa; Schulte, Carsten; Sharif, Bonita; Begel, Andrew; Hansen, Michael; Bednarik, Roman; Orlov, Paul; Ihantola, Petri; Shchekotova, Galina; Antropova, Maria (ICER)

Developing Coding Schemes for Program Comprehension using Eye Movements - Busjahn, Teresa; Schulte, Carsten; Kropp, Edna (PPIG)

Proceedings of the 9th Workshop in Primary and Secondary Computing Education, WiPSCE 2014, Berlin, Germany, November 5-7, 2014

The use of code reading in teaching programming - Busjahn, Teresa; Schulte, Carsten (Koli Calling)